2015
DOI: 10.1038/tp.2014.128
|View full text |Cite
|
Sign up to set email alerts
|

Aggrecan and chondroitin-6-sulfate abnormalities in schizophrenia and bipolar disorder: a postmortem study on the amygdala

Abstract: Perineuronal nets (PNNs) are specialized extracellular matrix aggregates surrounding distinct neuronal populations and regulating synaptic functions and plasticity. Previous findings showed robust PNN decreases in amygdala, entorhinal cortex and prefrontal cortex of subjects with schizophrenia (SZ), but not bipolar disorder (BD). These studies were carried out using a chondroitin sulfate proteoglycan (CSPG) lectin marker. Here, we tested the hypothesis that the CSPG aggrecan, and 6-sulfated chondroitin sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
154
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 100 publications
9
154
1
1
Order By: Relevance
“…12 schizophrenia Pantazopoulos et al, 2015). In a rat model of epilepsy, status epilepticus reduces PNN number and causes structural degradation of PNNs (McRae et al, 2012;McRae and Porter, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…12 schizophrenia Pantazopoulos et al, 2015). In a rat model of epilepsy, status epilepticus reduces PNN number and causes structural degradation of PNNs (McRae et al, 2012;McRae and Porter, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Dysregulation of PNNs is implicated in various neurological and psychiatric disorders including epilepsy, Alzheimer's disease, bipolar disorder, schizophrenia, and traumatic brain injury (Baig et al, 2005;McRae and Porter, 2012;Morawski et al, 2010;Okamoto et al, 2003;Pantazopoulos et al, 2015;Yi et al, 2012). Additionally, alteration of C6ST-1 expression and CS sulfation patterns are reportedly evident in brains of human patients with bipolar disorder or schizophrenia and mice with cortical brain injury (Okuda et al, 2014;Pantazopoulos et al, 2015;Yi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise Pantazopoulos and coworkers (2006) found that about one-third of PV+ interneurons in the human basolateral amygdala were ensheathed by WFA+ PNNs, and a subset of these neurons also expressed CB. The finding that there is significant loss of PNNs in the basolateral amygdala of patients with schizophrenia implicates these structures in the dysfunction of GABAergic neurons in this disorder (Pantazopoulos et al, 2010, 2015; Berretta, 2012; Berretta et al, 2015). …”
Section: Introductionmentioning
confidence: 97%
“…Several PNN proteoglycans, the lecticans, are highly glycosylated, and one, aggrecan, is highly enriched in mature PNNs (Bitanihirwe and Woo, 2014). The density of PNNs labeled with Wisteria floribunda agglutinin (WFA), a lectin that binds to specific carbohydrate moieties on proteoglycans, has been reported to be markedly lower in the entorhinal and prefrontal cortices in schizophrenia (Mauney et al, 2013;Pantazopoulos et al, 2010Pantazopoulos et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%